Impact of virtual-reality feedback on human balance training when using a haptic support surface in rehabilitation medicine - Krpič, Andrej (Elektrotehniški vestnik, 2014)
Balance training and postural response assessment have been for decades two separate tasks in the rehabilitation medicine. The former concerns physiotherapy and the latter diagnostics. The virtual-reality technology does not only enhance the possibilities of balance training, but in combination with a haptic floor enables the subjects to gain a postural imbalance experience. The differences in the kinematic postural responses of three neurologically intact young adults are examined during an active postural perturbation caused by a horizontal translation of the haptic floor without virtual-reality feedback. The response latencies are extracted from measurements of ankle, knee and hip joints kinematics from the onset of the perturbation. The results demonstrate significant differences for knee and hip joints kinematics, however a larger number of subjects should be studied to strengthen the findings.
Keywords: rehabilitacija; Rehabilitation; vocational rehabilitation; ravnotežje; Stroke; balance; možganska kap; navidezna resničnost; post-stroke